- #1

- 18

- 0

## Homework Statement

Assume that the Derivative Rule for Inverses holds. Given that f(x) = x + f(x), and g(t) = f

^{-1}(t), which of the following is equivalent to g'(t)?

a. g'(t) = 1 + t

^{2}

b. g'(t) = 1 + t

^{4}

c. g'(t) = 1 + g(x)

d. g'(t) = 1 / (1 + t

^{4})

## Homework Equations

## The Attempt at a Solution

This question popped up on my recent calc final and my friends and I cannot agree on what the answer is. I answered with C, and most of my friends answered D, arguing that the fraction makes it correct. Can somebody with more knowledge explain this to me? Thank you!